2008
DOI: 10.1007/s10840-008-9238-x
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term survival after pacemaker implant: Improved survival with right ventricular outflow tract pacing

Abstract: Outflow tract pacing appears to improve medium- and long-term survival. Prospective randomized trials with a greater amount of patients are necessary to confirm the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
0
12
0
3
Order By: Relevance
“…Unfortunately, the majority of the studies involved short-term follow-up studies. A recent retrospective study demonstrated a better survival in patients with RV outflow tract pacing as compared with RV apical pacing (81). The favorable effect of RV outflow tract pacing may be related to the more physiologic activation pattern, resulting in less LV dyssynchrony.…”
Section: Alternative Rv Pacing Sitesmentioning
confidence: 99%
“…Unfortunately, the majority of the studies involved short-term follow-up studies. A recent retrospective study demonstrated a better survival in patients with RV outflow tract pacing as compared with RV apical pacing (81). The favorable effect of RV outflow tract pacing may be related to the more physiologic activation pattern, resulting in less LV dyssynchrony.…”
Section: Alternative Rv Pacing Sitesmentioning
confidence: 99%
“…When RV pacing is inevitable, the His bundle [42,43], right ventricular outflow tract [44,45] and right ventricular septum [46,47] have been studied as alternate pacing sites. Selectively pacing these sites may reduce pacing induced ventricular dyssynchrony [48-50] and potentially result in a reduction in ventricular volumes with improved LV function compared to RV apical pacing.…”
Section: Minimizing the Detrimental Effects Of Rv Pacingmentioning
confidence: 99%
“…Исследования со стимуляцией из альтернативных то-чек (межжелудочковая перегородка, выходной тракт пра-вого желудочка) продемонстрировали спорные результа-ты [11,16,38,47]. В то же время бивентрикулярная стиму-ляция может иметь преимущества не только у пациентов с выраженной систолической дисфункцией, но и при со-хранной или умеренно сниженной ФВ ЛЖ [6,19,44].…”
Section: заключениеunclassified